2018
DOI: 10.1051/matecconf/201817805011
|View full text |Cite
|
Sign up to set email alerts
|

Product engineering design enhancing by parameterizing the 3D solid model

Abstract: The research approach and the case study presented in the paper are oriented towards the convergent use of a parametric modelling algorithm and of an advanced integrated CAD/CAE solution for the optimization of the product engineering design, for reducing the product life cycle environmental impact and for providing sustainability in product development. First of all, a conceptual model for the research framework is proposed, where the use of mathematical models (equations/mathematical relations, etc.) integra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…An important task is to make a bridge between the 3D design software and teaching software (CNN frame-work). The research related to 3D design can be found in various papers, e.g., about parameter enhancement in a 3D model [15], 3D CAD (Computer Aided Design) lightweight representation [16], or design process automation [17]. The automated sample generation from 3D models can be simplified using a web interface.…”
Section: Introductionmentioning
confidence: 99%
“…An important task is to make a bridge between the 3D design software and teaching software (CNN frame-work). The research related to 3D design can be found in various papers, e.g., about parameter enhancement in a 3D model [15], 3D CAD (Computer Aided Design) lightweight representation [16], or design process automation [17]. The automated sample generation from 3D models can be simplified using a web interface.…”
Section: Introductionmentioning
confidence: 99%